Women domination in the Galombang dance: between the customary idealism and the market use - Indrayuda, Indrayuda; Ardipal, Ardipal (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
This study aims to answer the women dominance in the Galombang dance creation in Minangkabau, West Sumatra from gender perspective. In addition, this study also reveals the position of women as an urgent thing in the Minangkabau dance creations, Galombang. This research used interdisciplinary approach, namely Cultural Sociology and Dance Anthropology. The data were obtained through various interviews, direct monitoring in the situation of the Galombang dance activity, and literature study to support the primary data. The analysis was done through ethnography method. The result of the research found that women dominance was bigger than men in the Galombang dance creations. In customary idealism, women are not Galombang dancers as the Galombang dance is intended for men. In reality, there is a bigger role between men and women in the Galombang dance; therefore, men’s role is not very decisive on the performance quality and selling value, as well as for the use of dance Galombang creations by society nowadays in West Sumatra.